The bacterial biocontrol agent Paenibacillus alvei K165 confers inherited resistance to Verticillium dahliae. (8th April 2021) - Gkizi, Danai; González Gil, Anna; Pardal, Alonso J; Piquerez, Sophie J M; Sergaki, Chrysi; Ntoukakis, Vardis; Tjamos, Sotirios E
Abstract : A bacterial biocontrol agent confers inherited resistance to plants and protects them against an agronomically important fungal pathogen. Abstract: The biocontrol agent Paenibacillus alvei K165 was previously shown to protect Arabidopsis thaliana plants against Verticillium dahliae . Here we show that K165 also confers inherited immune resistance to V. dahliae. By performing a histone acetyltransferases mutant screen, ChIP assays, and transcriptomic experiments, we were able to show that histone acetylation significantly contributes to the K165 biocontrol activity and establishment of inheritable resistance to V. dahliae. K165 treatment primed the expression of immune-related marker genes and the cinnamyl alcohol dehydrogenase gene CAD3 through the function of histone acetyltransferases. Our results reveal that offspring of plants treated with K165 have primed immunity and enhanced lignification, both contributing towards the K165-mediated inherited immune resistance. Thus, our study paves the way for the use of biocontrol agents for the establishment of inheritable resistance to agronomically important pathogens.